Advanced Carbon‐Based Nanocatalysts and their Application in Catalytic Conversion of Renewable Platform Molecules. Issue 11 (4th May 2022) - Chen, Zemin; Zeng, Xiang; Wang, Shenyu; Cheng, Aohua; Zhang, Ying
Abstract: The transformation of renewable platform molecules to produce value‐added fuels and fine‐chemicals is a promising strategy to sustainably meet future demands. Owing to their finely modified electronic and geometric properties, carbon‐based nanocatalysts have shown great capability to regulate their catalytic activity and stability. Their well‐defined and uniform structures also provide both the opportunity to explore intrinsic reaction mechanisms and the site‐requirement for valorization of renewable platform molecules to advanced fuels and chemicals. This Review highlights the progress achieved in carbon‐based nanocatalysts, mainly by using effective regulation approaches such as heteroatom anchoring, bimetallic synergistic effects, and carbon encapsulation to enhance catalyst performance and stability, and their applications in renewable platform molecule transformations. The foundation for understanding the structure‐performance relationship of carbon‐based catalysts has been established by investigating the effect of these regulation methods on catalyst performance. Finally, the opportunities, challenges and potential applications of carbon‐based nanocatalysts are discussed. Abstract : Catalysis with a small C : This Review introduces carbon‐based nanocatalysts for catalytic conversion of renewable platform molecules. Efficient and stable catalyst preparation methods are emphasized and the nanocatalysts are classified according to structure–performance relationships., with a view to framing a new route for the design of effective carbon‐based nanocatalysts.